Natural killer cells induce neutrophil extracellular trap formation in venous thrombosis. (16th December 2018) - Bertin, F.‐R.; Rys, R. N.; Mathieu, C.; Laurance, S.; Lemarié, C. A.; Blostein, M. D.
Abstract : Essentials Neutrophil extracellular traps (NETs) are generated during deep vein thrombosis (DVT). The role of interferon γ (IFNγ) and natural killer (NK) cells in NET formation was studied. IFNγ promote venous thrombosis through NET formation. NK cell depletion reduces DVT. Summary: Background: Neutrophils contribute to venous thrombosis through the release of neutrophil extracellular traps (NETs), but the mechanism triggering their formation remains unclear. In vitro data show that interferon (IFN)‐γ induces the formation of NETs. Objectives: To determine whether IFN‐γ and the transcription factor T‐box expressed on T cells (Tbet) promote venous thrombosis through neutrophil activation. Methods: Venous thrombosis was induced by flow restriction in the inferior vena cava in IFN‐γ −/−, Tbet −/− or wild‐type (WT) mice. After 48 h, thrombus size was measured by the use of high‐frequency ultrasound. NET formation was determined by immunofluorescence. Results and Conclusions: Thrombus formation was reduced in Tbet −/− and IFN‐γ −/− mice, suggesting that Tbet/IFN‐γ‐expressing cells are required for venous thrombosis. The number of NETs formed during thrombosis was significantly lower in Tbet −/− and IFN‐γ −/− mice. NET formation was also decreased in WT mice treated with an IFN‐γ‐blocking antibody. Injection of recombinant IFN‐γ into IFN‐γ −/− mice rescued the phenotype. Natural killer (NK) cells were specifically depleted prior to venous thrombosis induction. NK cell depletion results in decreased NET formation and smaller thrombi, suggesting that NK cells are required for thrombus development. In depleted mice, adoptive transfer of WT NK cells induced a similar thrombosis burden as in WT mice. In contrast, adoptive transfer of IFN‐γ −/− NK cells resulted in thrombi similar in size to those in depleted mice. In vitro, we showed that WT neutrophils released fewer NETs when they were cocultured with IFN‐γ −/− NK cells. This study demonstrates that NK cell‐dependent IFN‐γ production is crucial for thrombus development by promoting the formation of NETs by neutrophils.